2011
DOI: 10.1177/1368430210382427
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial behavior in diverse workgroups

Abstract: Many tasks in life cannot be accomplished without the help or cooperation of others: our loved ones, our colleagues, or just people in the street. The famous Beatles' song already suggests that we can achieve anything "with a little help from our friends." Indeed, most people are quite willing to help others that form part of their "ingroups," that is the groups with which they identify and that make up how they see themselves. We feel committed to members of our peer groups, our football team, or people that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 54 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Moreover, Vos and van der Zee [38] have suggested that individuals who prioritize interpersonal relationships with others, such as those with relational identity orientations, are more likely to engage in prosocial behaviors toward their workgroup members. Previous research has also shown that individuals with high levels of agreeableness and trait-positive affectivity are more likely to engage in prosocial behaviors involving deep acting and genuine displays [17,39].…”
Section: Self-identity Level As a Predictor Of Supervisor-directed Em...mentioning
confidence: 99%
“…Moreover, Vos and van der Zee [38] have suggested that individuals who prioritize interpersonal relationships with others, such as those with relational identity orientations, are more likely to engage in prosocial behaviors toward their workgroup members. Previous research has also shown that individuals with high levels of agreeableness and trait-positive affectivity are more likely to engage in prosocial behaviors involving deep acting and genuine displays [17,39].…”
Section: Self-identity Level As a Predictor Of Supervisor-directed Em...mentioning
confidence: 99%
“…When followers form relational identification to coworkers, they demonstrate behaviors that are beneficial to coworkers. Relational identification is associated with several processes that Pettigrew (1998) identified for overcoming intergroup bias, including empathy and perspective-taking (Aron et al, 1991), getting to know another person through personalized interactions (Brickson & Brewer, 2001), and behaving for the benefit of another person (Cooper, 2013;Vos & Van der Zee, 2011). Interpersonal organizational citizenship behavior (OCBI), a type of interpersonal altruistic behavior, directly helps to improve the effectiveness of peer, individual, and teams (Farmer et al, 2015).…”
Section: Leader Humility Multi-foci Relational Identification and Mul...mentioning
confidence: 99%
“…Despite the importance of information sharing to group performance, little is known about how cultural or racioethnic differences influence the extent to which group members share information within a heterogeneous group. Social categorization theory (Turner, 1985(Turner, , 1987 and social identity theory (Tajfel, 1978) suggests that group members will be more likely to help and share information with other members who are similar to themselves (also see Vos and van der Zee, 2011). However, it is possible that there are instances when individuals may be in groups in which there is no numerical majority thus reducing the likelihood that sub-groups will form.…”
Section: Indicators Of Inclusionmentioning
confidence: 99%
“…The western workplace is becoming more diverse, and social psychologists have a growing interest in understanding how this change influences team-based work within the organization (Christian et al, 2006;Van Veelen et al, 2013). Much of the diversity research is focused on the outcomes of work group (or team) diversity, which often offers mixed results, with some research revealing positive effects and others indicating negative or null effects of diversity (Bell et al, 2011;Cox et al, 1991;DeGrassi et al, 2012;McLeod et al, 1996;Oliveira and Scherbaum, 2015;Ruiz-Jimenez and del Mar Fuentes-Fuentes, 2016;Van Oudenhoven-van der Zee et al, 2009;Vos and van der Zee, 2011;Watson et al, 1993;Webber and Donahue, 2001). Furthermore, the focus of diversity research is largely on the outcomes of unit-level diversity, and there is relatively little research that seeks to understand the individual-level outcomes for persons working in diverse groups.…”
mentioning
confidence: 99%